PTU-268 Day-case loop ileostomy closure: feasible, safe and efficient. (22nd June 2015) - Bhalla, A; Peacock, O; Williams, J; Tou, S; Hurst, N; Speake, W; Tierney, G; Lund, J
Abstract : Introduction: Over 5, 000 loop ileostomy closures were performed within the United Kingdom in 2013 with a median inpatient stay of 5 days. Previously we have successfully implemented a 23-hour protocol for loop ileostomy closure which was modified to create one specific for same-day discharge. We present our early experience of day-case loop ileostomy closure. Method: A specific patient pathway for day-case discharge following loop ileostomy closure was implemented at a single UK institution. Inclusion criteria conform to British Association of Day Surgery guidelines. Exclusion criteria include post-operative chemo-radiotherapy, multiple co-morbidities and social care needs. Follow-up consisted of telephone contact (24 and 72 h post-discharge) and a routine outpatient appointment. Patients were provided with a 24 h contact point in case of emergency. Results: Fifteen patients were enrolled (12 males; median age 67 years (39–80); median operating time 41 min (23–80)). Thirteen patients had ileostomy formation during low anterior resection for adenocarcinoma, one patient had an ileostomy fashioned during reversal of Hartman's procedure and one for a function bowel disorder. Median time from primary procedure to day-case loop ileostomy closure was 8 months (3–14 months). Every patient was discharged on the day of surgery. There were no complications related to surgery, and one readmission with urinary tract infection. Median length of follow-up was 4 months (2–16 months). Conclusion: Our early experience shows day-case loop ileostomy closure is feasible, safe and efficient. This protocol will become standard within our institution for suitable patients, saving on average 5 inpatient bed days per patient. Disclosure of interest: None Declared.